Implementasi Kurikulum Pendidikan Anak Usia Dini Berorientasi Peningkatan Kemampuan Kognitif Dan Sosial Keagamaan Anak - Malisatul Mar'ah; Malisatul Mar'ah (Oasis : Jurnal Ilmiah Kajian Islam, 2023)
The PAUD curriculum gives direction to the stimulation process that is carried out carefully, carefully, according to the characteristics of the child and assessed comprehensively from authentic data. This study aims to analyze the implementation of the 2013 Curriculum for Early Childhood Education at RA Al-Hidayah, TK Tunas Bhakti Pertiwi and Kober Anggia Putra. In the implementation of early childhood education, the 2013 PAUD curriculum plays a very important role as a tool to achieve educational goals. However, in its implementation there are still various obstacles. The purpose of this study is to analyze and explain the implementation of the Early Childhood Education curriculum which is oriented towards increasing children's cognitive and socio-religious abilities. The research method uses a descriptive method. The data collection instrument used observation, interviews and document studies. The analysis technique is done through data reduction, data display and data inference. The findings of this study indicate that one way is by conducting trainings with the aim of providing socialization related to the implementation and management of PAUD curriculum management, especially in RA, TK and Kober. The existence of expert presentations, discussions, and questions and answers went well so that RA, TK and Kober teachers could face problems regarding the implementation of the curriculum that had been carried out so far.